Collaboration and Technology 18th International Conference, CRIWG 2012, Raesfeld, Germany, September 16-19, 2012, Proceedings - Herskovic, Valeria; Hoppe, H. Ulrich; Ziegler, Jürgen; Jansen, Marc (Information Systems and Applications, incl. Internet/Web, and HCI, 2012)
This book constitutes the proceedings of the 18th Collaboration Researchers' International Working Group Conference on Collaboration and Technology, held in Raesfeld, Germany, in September 2012. The 9 revised papers presented together with 12 short papers were carefully reviewed and selected from numerous submissions. They are grouped into five themes that represent collaborative learning, social media analytics, conceptual and design models, formal modeling and technical approaches and collaboration support in emergency scenarios.